Lecturers’ Professionalism in Shaping Students' Perceptions and Commitments - Susanto, Ratnawati (LPPM Undiksha, 2019)
The Institute of Teachers’ Education or Lembaga Pendidikan Tenaga Kependidikan (LPTK) have some following strategic issues: (1) teacher graduates who perform poor professionalism, (2) LPTKs that do not meet quality standard, (3) the insufficient education of the teacher students that fails to create professional teachers. The research was carried out at a Faculty of Teacher Training and Education/Fakultas Keguruan dan Ilmu Pendidikan (FKIP) in West Jakarta. The research subjects were the lecturers and senior year active students, consisting of 191 students, who were selected through saturated samples. This research employed a mixed-method design using causal survey. The data were collected in the form of a questionnaire. The results of the study showed that the lecturers’ professionalism has impacts to the development of the students' perceptions and profession commitments